Unlocking B2B Purchase Engagement: Investigating Its Drivers and Consequences in App-Based Service Subscriptions for MSMEs - Arief, Faisal; Salehudin, Imam (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to highlight the role of purchase engagement in the business-to-business (B2B) context, which is mainly under-explored due to the intricacy and diverseness of stakeholders embroiled in B2B purchasing decisions. This paper fills the gap by studying purchase engagement in the Micro, Small, and Medium Enterprises (MSMEs) B2B setting, particularly for app-based service subscriptions. Design/Methods/Approach: The study recruited responses from 215 MSME owners and managers, current customers of a subscription-based point-of-sales (POS) service. The PLS-SEM technique empirically validated the conceptual framework and the research hypotheses. Findings: The findings indicate that the conceptual model of customization, identification with virtual communities, and loyalty to account managers are exogenous factors influencing purchase engagement, perceived dependency, and willingness to pay for price premiums. Originality/Value: This study aims to understand purchase engagement in B2B, focusing on transactional drivers. This framework also investigates a particular set of drivers and results from purchase engagement factors in B2B app-based service subscriptions. Practical/Policy implication: B2B app-based service subscription stakeholders must ensure that all efforts to engage with customers strengthen their dependency on the service by starting with purchase engagement, customization, identification with virtual communities, and loyalty to account managers.